Estudo, por análise térmica, da estocagem do bagaço de cana - Santos, Moacyr Lopes dos (2007)
In this essay it was valuated the thermical estability of the sugar cane bagasse during the storage process for ulterior burning in boiler. The bagasse samples were collected at Usina Caeté (MG), from several places or points of the storage rall, very after the passage through the millstone of syrup extracting, and, also in natural bagasse samples, dry and moist for 150 days. The results of thermogravimetry (TG), differential thermal analysis (DTA) and the differential scanning calorimetry (DSC) of the samples were obtained in one equipment SDT Q600 with simultaneous analysis (TG/DTA/DSC), with a level of heating from 25 to 600 o C, where it was observed that during the bagasse storage, whether being humid of dry, it occurs loss up till 32 % in the biomass calorific power. This is caused by the decomposition of its components, mainly the cellulose which suffers loss in mass from 15% and 28 %, respectivelly, in dry bagasse and humid one, outpointing that the energetic content from the bagasse is much more profitable as soon as it is ready or in other words, imediately after the extration of sugarcane syrup. Keywords: Thermal Analysis, sugar cane bagasse, cellulose.